Penanggulangan Stunting Melalui Modal Sosial di Desa Besmarak Kecamatan Nekamese Kabupaten Kupang - Nursalam N; Melkisedek N.B.C. Neolaka; William Djani; Hendrik Toda (Idea Pengabdian Masyarakat, 2021)
Stunting is one of the public problems that need attention and handling. The incidence of stunting if leftunchecked  can have  implications  for  the  quality  of human  resources,  namely in  addition  to  risking  physicalgrowth barriers and children's vulnerability to disease, it also causes cognitive development barriers that will affectchildren's intelligence and productivity levels in the future. The community service (PPM) which is carried out in theform of counseling in Besmarak village, Nekamese sub-district, Kupang regency is expected to provide knowledgeto  the  community  that  solving  the  stunting  problem  is  not  only through health and nutrition improvementassistance provided by the government, but also through community social capital, namely through social networksand  community trust norms.  There  is a  strong  relationship between social capital and  solving  various  publicproblems, so that people with higher social capital also have higher awareness, they are able to take collectiveaction in preventing stunting.